Analog circuits for VLSI neural networks - Lee, See Taur. (2009)
Rapid advances in the semiconductor industry have provided the technologies for the implementation of millions of transistors on a single chip. Thus, state-of-the-art VLSI technology and future ULSI (Ultra Large Scale Integration) technologies are, and will be. a good implementation medium for artificial neural network circuits. The complexity of a single chip and the clock frequency of a system may not increase unchecked, therefore restricting the maximum performance of sequential computers. The artificial neural network is one of many approaches to enhance the computational capabilities in high-speed information processing.